2015
DOI: 10.1007/s11430-015-5121-7
|View full text |Cite
|
Sign up to set email alerts
|

The causal sequence investigation of the ring current ion-flux increasing and the magnetotail ion injection during a major storm

Abstract: Comprehensive records are available in ENA data of ring current activity recorded by the NUADU instrument aboard TC-2 on 15 May, 2005 during a major magnetic storm (which incorporated a series of substorms). Ion fluxes at 4-min temporal resolution derived from ENA data in the energy ranges 50-81 and 81-158 keV are compared with in situ particle fluxes measured by the LANL-SOPA instruments aboard LANL-01, LANL-02, LANL-97, and LANL-84 (a series of geostationary satellites that encircle the equatorial plane at ~… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
(35 reference statements)
1
4
0
Order By: Relevance
“…It is suitable for a tracer particle of ring current energetic ion distribution. The intensity and distribution of an ENA flux in different orbital positions are predicted by simulation, which is similar to the previous telemetry instrument design [Lu et al, 2014]. The simulation of ENA imaging was carried out in four positions in lunar orbit: new moon, first quarter, full moon, and last quarter (Figure 1, top).…”
Section: Moon-based Ena Imaging Measurement Simulationsupporting
confidence: 65%
See 1 more Smart Citation
“…It is suitable for a tracer particle of ring current energetic ion distribution. The intensity and distribution of an ENA flux in different orbital positions are predicted by simulation, which is similar to the previous telemetry instrument design [Lu et al, 2014]. The simulation of ENA imaging was carried out in four positions in lunar orbit: new moon, first quarter, full moon, and last quarter (Figure 1, top).…”
Section: Moon-based Ena Imaging Measurement Simulationsupporting
confidence: 65%
“…The present inversion results with the highest time resolution (~1 min) are derived from TC-2/NUADU [Lu et al, 2019] and are applied to the causal sequence analysis of particle events and environmental disturbances during geomagnetic activity. By comparing 4-min time resolution ENA image sequence with LANL's in situ measurements, Lu et al [2016] have found that ring current energetic ions increase before ion injection from the magnetotail, which challenges the existing concept that ring current particles are injected earthward from the magnetotail.…”
Section: Introductionmentioning
confidence: 93%
“…The low-altitude polar ENA enhancement caused by substorms often appears before midnight and is accompanied by eastward drift. When the ENA-enhanced signal decays, it will be accompanied by westward movement [21,22]. Thus, we mimic the substorm growth phase with the Kp index ascending sequence of the simulation images at the full moon and the first quarter (Figures 5 and 6).…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Those improved temporal and spatial resolutions could enable monitoring not only the global energetic ion flux distribution but also to obtain the causal sequence analysis of the transport process of energetic ions during periods of high geomagnetic activity period (Lu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the near-Earth polar orbit satellites can be used to realize real-time monitoring of ring current energetic ions during geomagnetic activities with high spatial and temporal resolution. In the present work, we attempt to apply this imaging measurement to the evolution process of energetic ion events (Lu et al, 2016(Lu et al, , 2019. The main scientific objective of this work is to use the ENA imager on a polar orbit satellite to monitor the distribution and evolution of energetic particles in the inner and outer radiation belts, especially for small-substorm events; serving space weather forecasting with mass data statistics; to explore the causality of energetic ion precipitation, injection, and other transport processes, as well as the electromagnetic field environmental evolution.…”
Section: Introductionmentioning
confidence: 99%